Memory and Forgetting in a Time of Violence: Brian Friel’s Meta-History Plays - Tony Crowley (Estudios Irlandeses, 2008)
In the 1980s, Brian Friel, one of Ireland’s most successful twentieth century dramatists, authored two plays – Translations and Making History  – which were concerned with major events in colonial history. Given the context in which the plays were written – Northern Ireland was in a state of war at the time – the playwright’s choice of topics (the introduction of the National Schools and the Ordnance Survey in the nineteenth century and the failed Gaelic revolt against English rule and the Flight of the Earls in the sixteenth and seventeenth centuries) was both pointed and politically contentious. Yet, the argument of this essay is that rather than presenting versions of the past which conform to the ideological imperatives of a particular political stance, Friel’s plays are much more interesting and significant in that they provoke a whole series of questions around the issue of historical representation. One of the most important of those questions is the applicability of the criteria truth and falsity in historical and other modes of interpretation. The essay concludes with a consideration of the politics of memory and forgetting in contemporary Northern Ireland.